About face : - Cooper, Alan (Wiley Pub., 2007)
This completely updated volume presents the effective and practical tools you need to design great desktop applications, Web 2.0 sites, and mobile devices. You’ll learn the principles of good product behavior and gain an understanding of Cooper’s Goal-Directed Design method, which involves everything from conducting user research to defining your product using personas and scenarios